Pengaruh Desain Post, Komunikasi Visual dan Iklan Online Terhadap Minat Beli Pada Instagram @kopikenangan.id - Tristanti, Denia; Oetarjo, Mas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
As technology develops, especially Instagram has become an essential need in increasing work productivity and has become the main platform for promoting business in Indonesia. One brand that uses Instagram is Kopi Kenangan. When marketing, you need to pay attention to post design, visual communication and online advertising. This encourages researchers to examine what variables influence buying interest. “This study aims to investigate the influence of variables on enhancing purchase interest on Instagram @kopikenangan.id. The research adopts a quantitative approach with primary data. Respondents were selected using the Lemeshow formula, resulting in a sample size of 100 individuals. Data analysis involved multiple linear regression, as well as validity, reliability, normality, multicollinearity, and heteroskedasticity testing, along with T-tests and F-tests. The findings indicate that post design, visual communication, and online advertising significantly impact consumer purchase interest on the Instagram account @kopikenangan.id.